Immunization Status of Children and Its Association with Maternal Education - Muhammad Ahmed , Maria Sharif , Ali Sufyan , Mudassir Sharif Bhatti , Rai Muhammad Asghar, Muhammad Ahmed , Maria Sharif , Ali Sufyan , Mudassir Sharif Bhatti , Rai Muhammad Asghar (Students' Supplement of Journal of Rawalpindi Medical College, 2022)
Background: The Expanded Programme onImmunization was implemented in Pakistan in 1978in collaboration with WHO and UNICEF. Pakistanbeing a developing country is still struggling to meetits goals. Educational status and knowledge of themother has a key role in the success of immunizationprogramme. Objective: To assess the immunization status ofchildren and the impact of maternal level ofeducation on the immunization status of childrenbetween the ages of 15-36 months at RMU AlliedHospitals. Methods: A cross sectional study was conducted on380 respondents visiting Outpatient Department ofPaediatrics, RMU allied hospitals. Mothers of thechildren of age group 15-36 months were included inthe study via non-probability consecutive samplingtechnique and were interviewed using a structuredquestionnaire. Statistical data was analyzed usingSPSS version 23.Results: 303 (79.7%) of the children were fullyimmunized, 66 (17.9%) were partially immunizedand 11 (2.9%) had not received any immunization.115 (68.04%) children of illiterate mothers, 145(87.7%) children of mothers with education up tomatriculation and 43 (93.47%) children of motherswith higher education were fully vaccinated.Conclusion: Vaccination status of childrenpresenting at RMU allied hospitals was quitesatisfactory. Mothers who have attained a higherdegree of education are more likely to completelyvaccinate their child as compared to those with alower level of education or those who areuneducated. Keywords: EPI, Immunization status, Vaccination,Maternal Education